Сhronology of the Karakiyasay II rock art - Kashchey O.A.; Nedashkovsky L.F. (Вестник археологии, антропологии и этнографии, 2023)
The article provides a brief description of the history of the study and characteristics of six large assemblages with petroglyphs of the Karakiyasay complex, located on the southern slopes of the Karzhantau mountain ridge (North-Eastern Uzbekistan). Currently, about 600 stones and rock outcrops with more than 3700 images have been identified within the site. The most interesting is the organization of the pictorial series of one of the assemblages — Karakiyasay II, on the materials of which, using cluster, planigraphic and stratigraphic analyses, it was possible to carry out the chronological attribution of almost all images of this section of the complex. For this, the semantic units of the organization of the visual series of the assemblage were initially designated, including single and paired images, multi-figure “scenes” and plot compositions. Then, for the most numerous images — 169 figures of the Siberian mountain goat, by the means of measuring the figures and calculating the ratios of a various quantities characterizing the proportions of the design of body parts of the animals — the ratio of the body height, length of the legs, neck and head to the length of the body, as well as by introducing quantities containing numerical indicators of the way animals are depicted (number of horns, number of legs, turn of the figure, angle of the legs, angle of the neck) — nine quantitative characters were determined. The next stage is the cluster analysis, which allowed us to identify three clusters (groups) of similar figures of mountain goats. Since the data obtained in the first two clusters turned out to be heterogeneous, they were also subjected to cluster analysis, as a result of which it was possible to identify nine types of figures characterized by a number of similar features. Later, using the analysis of planigraphy and stratigraphy, the accuracy of the identified types was verified, their chronological sequence was determined, and, based on the analogies with the manner of completion of figures in these types, the chronological attribution of the entire pictorial series of the site was carried out. The results of the study indicate that the petroglyphs in the Karakiyasay II assemblage were created mainly in the Late Bronze Age (the second half of the 2nd mil. BC — beginning of the 1st mil. BC) — Early Iron Age (7th c. BC — 4th c. AD).